Pengaruh Penggunaan Filter pada Strainer Terhadap Usia Pakai Filter Bahan Bakar Mesin Diesel 6374 CC - Sidqi Hidayat Tulloh; Purwoko Purwoko (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
Indonesia has implemented a policy of using biodiesel with a 30% biodiesel content, known as B30. The use of biodiesel also tends to have deposits that can clog fuel channels and filters. This can cause serious problems in the fuel system, especially blockages in the fuel filter. This research aims to find out which filter on the strainer is the most optimal in increasing the service life of the fuel filter on the 6374 CC diesel engine. In this study, the research approach used was a quantitative experimental type. The independent variable used in this research is the size of the filter on the strainer, namely 10 µm, 18 µm, and 20 µm, and the dependent variable is the service life of the fuel filter. With the data collection method using a filter density test tool. The data obtained was then processed into graphic data and analyzed using the one way anova method. The research results show that all strainer filters are able to increase filter life from 1,702 km to 5,106 km. The strainer filter with a size of 18 µm at km 5,106 is the most optimal filter. This happens because this filter does not require routine cleaning at every round-trip vehicle operation like a 10 µm size strainer filter and the discharge is slightly higher than a 20 µm size strainer filter.